Supporting the Paralympic athlete: Multi-disciplinary reflections - Goosey-Tolfrey, V. L.; Naylor, M.; Bond, K. (2009 BASES Annual Conference, 2009)
Great Britain has a Paralympic Squad to be proud of. In Beijing 2008 the team returned with a total of 102 medals (42 Gold, 29 Silver and 21 Bronze). There are 20 Paralympic summer sports and five winter sports which allow athletes, with a range of disabilities to compete. The main categories include wheelchair athletes with a variety of different disabilities - amputees, visually impaired athletes, dwarfs, and athletes with cerebral palsy. Some sports had large squads with an impressive support team in place to provide sports science and medical support. Whilst other squads accessed sports science through the ParalympicsGB consultants. Either way all athletes are aware of how sport science can help them to maximise their performance through biomechanical, physiological, nutritional, strength and conditioning and psychological intervention. This symposium will provide an multi-disciplinary discussion on the biomechanical, physiological/nutritional and psychological aspects of support leading into and during these games using examples from wheelchair sports, swimming and archery.